2020
DOI: 10.1158/1541-7786.mcr-19-1082
|View full text |Cite
|
Sign up to set email alerts
|

The NF-κB Pathway Promotes Tamoxifen Tolerance and Disease Recurrence in Estrogen Receptor–Positive Breast Cancers

Abstract: The purpose of this study was to identify critical pathways promoting survival of tamoxifen-tolerant, estrogen receptor  positive (ER+) breast cancer cells, which contribute to therapy resistance and disease recurrence. Gene expression profiling and pathway analysis was performed in ER+ breast tumors of patients before and after neo-adjuvant tamoxifen treatment and demonstrated activation of the NFκB pathway and an enrichment of EMT/stemness features.Exposure of ER+ breast cancer cell lines to tamoxifen, in v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
2
26
0
1
Order By: Relevance
“…The activity of NF‐κB is suppressed by COUP-TFII and decreased COUP-TFII expression results in an endocrine-resistant phenotype ( 107 ). The NF‐κB signaling pathway inhibitor (ACT001) in combination with tamoxifen hinders the proliferation of tamoxifen-resistant cells ( 108 ), hence NF-κB inhibition plays a promising approach to prevent tamoxifen resistance ( 109 ).…”
Section: Endocrine Resistancementioning
confidence: 99%
“…The activity of NF‐κB is suppressed by COUP-TFII and decreased COUP-TFII expression results in an endocrine-resistant phenotype ( 107 ). The NF‐κB signaling pathway inhibitor (ACT001) in combination with tamoxifen hinders the proliferation of tamoxifen-resistant cells ( 108 ), hence NF-κB inhibition plays a promising approach to prevent tamoxifen resistance ( 109 ).…”
Section: Endocrine Resistancementioning
confidence: 99%
“…Kastrati at al. ( 35 ) reported that NF-κB pathway promotes tamoxifen tolerance and disease metastasis in estrogen receptor-positive BRCAs.…”
Section: Chemoresistance Mechanisms In Brcamentioning
confidence: 99%
“…It is tempting to speculate that the reduced recurrence and breast cancer-related mortality in patients who receive tamoxifen for 10 years compared to only 5 years (Davies et al, 2013;Gray et al, 2013) is due to a sustained EMP-induced dormant state. Indeed, evidence has accumulated that endocrine therapy induces EMT signatures in ER+ BC (Creighton et al, 2009;Kastrati et al, 2020;Sflomos et al, 2016).…”
Section: Discussionmentioning
confidence: 99%